PENGATURAN INDIKASI GEOGRAFIS TERHADAP PRODUK WINE SALAK BEBANDEM KARANGASEM - apriliani, kadek; Sudirga, Made; Putra, Putu Angga Pratama; Darsana, Kadek Damayani Indriamitha; Krisnadewi, Anak Agung Putri (Jurnal Yustitia, 2024)
Geographical indication (GI) is a form of legal protection that gives products a distinctive identity based on their geographical origin. In Indonesia, GI has been applied to various products, including locally processed products such as Burdendem Karangasem salak wine. This article discusses the IG regulation of the Burdendem Karangasem salak wine product and its impact on the agricultural industry and local economy. Burdenem Karangasem salak wine is a unique product produced from salak fruit typical of the Karangasem area, Bali. IG provides protection for this geographical name, ensuring that only products originating from the area can use the label "wine salak Banyakem Karangasem." This provides a double benefit: protecting product identity and encouraging local economic development. With the IG arrangement, salak farmers in Karangasem get incentives to maintain the quality and authenticity of their products. This increases farmers' incomes and helps preserve local agricultural heritage. In addition, IG is opening up greater export opportunities for Burdendem Karangasem salak wine, presenting a promising business opportunity. This article also discusses challenges in regulating GI, such as monitoring and law enforcement, as well as collaborative efforts between government, farmers and industry players. In the context of globalization, it is important to maintain the authenticity of local products while promoting economic growth. IG's regulation of Bandem Karangasem salak wine is a successful example of this effort and can be an inspiration for other geographically based products.